EFEKTIFITAS RHIZOCTONIA MIKORIZA DALAM MENGINDUKSI KETAHANAN ANGGREK PHALAENOPSIS AMABILIS TERHADAP FUSARIUM SP. - R. Soelistijono (JURNAL ILMIAH AGRINECA, 2014)
This study examines the effectiveness of mycorrhizal Rhizoctonia resistance induction in Phalaenopsis amabilis against Fusarium sp. Fusarium solani is known as pathogens that attack many orchids P. amabilis (Chung et al., 2011) compared to other pathogenic fungi. Attack of Fusarium sp. will cause rot and yellow colored leaves. Until now there has been known as a biological control orchid against Fusarium sp. In this study tested the endurance locations in Sleman and Surakarta to see the effectiveness of a good orchid growth induced by Rhizoctonia mycorrhizal or not to attack by Fusarium sp. The results of the study showed that mycorrhizal Rhizoctonia able to inhibit the attack of Fusarium sp. It is shown by the value of the index of disease resistance Â (DSI) in P. amabilis orchid mycorrhizal Rhizoctonia induced lower than that not induced. Mycorrhizal Rhizoctonia induction results in Sleman provide a more real than mycorrhizal Rhizoctonia induction in Surakarta.